2018
DOI: 10.1002/hbm.24439
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural development and cognitive ability in the first 2 years of life

Abstract: White matter (WM) integrity has been related to cognitive ability in adults and children, but it remains largely unknown how WM maturation in early life supports emergent cognition. The associations between tract‐based measures of fractional anisotropy (FA) and axial and radial diffusivity (AD, RD) shortly after birth, at age 1, and at age 2 and cognitive measures at 1 and 2 years were investigated in 447 healthy infants. We found that generally higher FA and lower AD and RD across many WM tracts in the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 57 publications
(94 reference statements)
5
28
0
1
Order By: Relevance
“…Importantly, this study was able to demonstrate that interindividual variation in FA in tracts associated specifically with language function (the CC and left AF) already in neonates is meaningfully associated with language acquisition, despite the fact that major features of this ability are largely absent at birth. This is in line with recent findings by Girault et al (2019), who found that white matter microstructural development in tracts including the AF in newborns was associated with cognitive development as assessed using the Mullen Scales of Early Learning generally, as well as language development as assessed by Mullen Scales of Early Learning subscales specifically. Girault and colleagues chiefly found associations between infant cognitive outcomes and neonatal white matter maturation as assessed by axial diffusivity, a DWI measure assessing longitudinal diffusivity along the tensor ellipsoid Cluster size is indicated by the number of consecutive points in that cluster significantly associated with language outcomes; percentage of tract represents the overall percentage of tract represented by cluster; corrected peak significance in cluster; and beta value at peak significance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Importantly, this study was able to demonstrate that interindividual variation in FA in tracts associated specifically with language function (the CC and left AF) already in neonates is meaningfully associated with language acquisition, despite the fact that major features of this ability are largely absent at birth. This is in line with recent findings by Girault et al (2019), who found that white matter microstructural development in tracts including the AF in newborns was associated with cognitive development as assessed using the Mullen Scales of Early Learning generally, as well as language development as assessed by Mullen Scales of Early Learning subscales specifically. Girault and colleagues chiefly found associations between infant cognitive outcomes and neonatal white matter maturation as assessed by axial diffusivity, a DWI measure assessing longitudinal diffusivity along the tensor ellipsoid Cluster size is indicated by the number of consecutive points in that cluster significantly associated with language outcomes; percentage of tract represents the overall percentage of tract represented by cluster; corrected peak significance in cluster; and beta value at peak significance.…”
Section: Discussionsupporting
confidence: 92%
“…The maturation of the superior longitudinal fasciculus-AF complex, which connects the inferior frontal gyrus with the superior temporal gyrus/sulci and the inferior parietal lobule, has been shown to correlate with the ability to comprehend complex sentence structures in children aged 3 to 10 years (Skeide et al, 2015). More recently, Girault et al (2019) showed that white matter microstructural development in regions including arcuate tracts at the neonatal time point was associated with receptive language development at 1 and 2 years in healthy children. Both the CC and AF play a role in language processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the codevelopment of these two longitudinal processes has been of recent interest (Girault et al, 2019;Jolles et al, 2016). The nature of the codevelopment of these two longitudinal processes has been of recent interest (Girault et al, 2019;Jolles et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, less known about the time-evolution of the relationship between brain structure and cognitive development, which was the primary motivation for our study. The nature of the codevelopment of these two longitudinal processes has been of recent interest (Girault et al, 2019;Jolles et al, 2016). Previous modeling of the relationship between white matter and cognitive development is sparse and has been cross-sectional (Nagy, Westerberg, & Klingberg, 2004), considered a few age bins (Dubois et al, 2008;Jolles et al, 2016), or used parametric random effects models to provide longitudinal summaries for trajectory clustering .…”
Section: Introductionmentioning
confidence: 99%